An Ovarian Tumour - Wasif, Afsheen; Gupta, Limci (International Journal of Pathology, 2018)
A 46 year old lady with history of hypertension, hyperlipidemia, Type 2 diabetes, cardiovascular accidents, asthma, polycystic ovaries and seizures presented with nine weeks history of constipation which failed to resolve with standard laxatives. She had an ultrasound scan which revealed a huge (30 cm) complex cyst occupying the pelvis and abdomen. She was then referred to the gy-naecologist and MRI scan was requested at that point. A week after, she was admitted via acci-dent and emergency department with vomiting, shortness of breath, urinary frequency and diffi-culty in lying flat with a large palpable abdom-inopelvic mass.